Pengaruh mimosa pada penyamakan kulit jaket domba samak nabati menggunakan sistem C-RFP, ditinjau dari sifat organoleptis, fisis, dan morfologi kulit - Sutyasmi, Sri; Widowati, Titik Purwati; Setyadewi, Noor Maryam (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2016)
The purpose of this study was to determine the effect of the use of mimosa, to manufacture environmentally friendly leather for jacket by using the C-RFP system (C=Conditioning, R=Rapid, F=Fass (drum), P=Powder), on physical, organoleptic, and morphology properties of leather. It was also to obtain a formula for vegetable tanning with C-RFP system. Pickled skins are conditioned (pre-tanning) using Sodotan TSN and Sodotan APR, and then Sodotan TSN was chosen due to it meets the requirements of SNI leather for jacket (SNI 4593:2011). Then, pickled skins were tanned with mimosa and applied C-RFP system or rapid tanning without water added. Mimosa, used in this research, were 15%, 20%, and 25% and fatliquor were 12.5%, 15%, and 17.5%. Furthermore, The leather were finished into an environmentally friendly leather for jackets, and then tested for physical and organoleptic properties based on the SNI 4593:2011 as well as leather morphology (SEM). The physical test result shows that for mimosa 15%, 20% and 25%, and for fatliquor 15% and 17.5% are fullfill the SNI.